2022
DOI: 10.3390/life12070925
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic Aldehydes in the Earth’s Crust—Remains of Prebiotic Chemistry?

Abstract: The origin of life is a mystery that has not yet been solved in the natural sciences. Some promising interpretative approaches are related to hydrothermal activities. Hydrothermal environments contain all necessary elements for the development of precursor molecules. There are surfaces with possible catalytic activity, and wide ranges of pressure and temperature conditions. The chemical composition of hydrothermal fluids together with periodically fluctuating physical conditions should open up multiple pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Information about the typical chemistry of the fluids from the fault zones can be determined by analysing the fluid inclusions in hydrothermally formed fissure minerals. These minerals were previously found both in archaic hydrothermal quartz minerals of Western Australia and in the most recent fissure calcites in the vicinity of sub-recent volcanoes in the Eifel [5,28].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Information about the typical chemistry of the fluids from the fault zones can be determined by analysing the fluid inclusions in hydrothermally formed fissure minerals. These minerals were previously found both in archaic hydrothermal quartz minerals of Western Australia and in the most recent fissure calcites in the vicinity of sub-recent volcanoes in the Eifel [5,28].…”
Section: Introductionmentioning
confidence: 69%
“…Through Fischer/Tropsch-like synthesis and other processes (e.g., the Haber-Bosch process), organic molecules, which are a prerequisite for the development of life, could be formed from abiotic starting materials. Starting substances for lipids, such as aldehydes, were found in the fluid inclusions of hydrothermal archaic quartz minerals and in recent hydrothermal calcites [5,28]. Hennet et al (1992) showed that under simulated hydrothermal conditions (150 °C, 10 Atm, pH 7) with various mineral catalysts, amino acids could be formed from the starting compounds of the fluids (formaldehyde, ammonia, cyanide) [29].…”
Section: Environment and Resourcesmentioning
confidence: 99%